2001
DOI: 10.1002/app.10038
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐catalyzed liquefaction of waste paper in the presence of phenol and its application to Novolak‐type phenolic resin

Abstract: Liquefaction of waste paper (WP) was performed in the presence of phenol with an acid catalyst. Newspaper (NP) was liquefied more easily than box paper (BP) or business paper (BNP). Differences in the degree of liquefaction were due to different chemical compositions. That is, NP had a relatively high lignin content, which is known to be easily liquefied, whereas BP and BNP were mainly composed of cellulose with a crystalline structure, which is difficult to liquefy. The acid concentration and phenol/WP ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…This is the reason that when the reaction yield increases, the peak at 1728 cm À1 , which is related to the lignin network, is not observed in the residue. This finding is in agreement with the findings of Lee et al [18] and Sejin and Shiraishi [19] , which showed that among the three major components of wood at least the majority of lignin was liquefied rapidly.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This is the reason that when the reaction yield increases, the peak at 1728 cm À1 , which is related to the lignin network, is not observed in the residue. This finding is in agreement with the findings of Lee et al [18] and Sejin and Shiraishi [19] , which showed that among the three major components of wood at least the majority of lignin was liquefied rapidly.…”
Section: Resultssupporting
confidence: 94%
“…This result indicates that liquefaction of crystalline cellulose with phenol is difficult in comparison with other components of EFB. This finding is in agreement with findings of Lee et al [18] and Sejin and Shiraishi [19] , which showed that among the three major components of wood, the cellulosic component that possesses crystalline structure is the most resistant component in the liquefaction process. The result also indicates that the accessibility of EFB increases using strong acids, such as hydrochloric acid and sulfuric acid.…”
Section: Resultssupporting
confidence: 93%
“…It should, thus, be possible to decrease the cost of glucose and utilize it in industrial scale without consuming food resources. Polyols produced from wood flour cellulose [22], corn bran [23] and waste paper [24] have already been utilized to synthesize different polymers, mainly thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…During the period of liquefaction with phenol as a solvent, the chemical components of biomass will be degraded and decomposed to various oligomers and monomers and will react with phenol to form hydroxyl benzyl derivatives containing the phenolic functional groups, which can react with formaldehyde, just like phenol (Lin et al 2001;Zhang et al 2006). The phenolliquefied biomass is suitable as raw material to prepare novolak-type PF resins (Lin et al 1995;Alma et al 1996;Lee et al 2002a;Lee and Chen 2008;Lee et al 2009) and resoltype PF resins (Lee et al 2002b;Hassan et al 2009), which can be utilized for moldings or adhesives. However, their applicability as raw materials to prepare spherical PF beads is not known.…”
Section: Introductionmentioning
confidence: 99%